Proteomic profiling identifies upregulation of aurora kinases causing resistance to taxane-type chemotherapy in triple negative breast cancer - Bohan Ning; Chang Liu; Ali Cem Kucukdagli; Jiuyi Zhang; Han Jing; Zhiqian Zhou; Yuwei Zhang; Ying Dong; Yunjia Chen; Hua Guo; Jia Xu (Scientific Reports)
Abstract Nowadays, chemotherapy and immunotherapy remain the major treatment strategies for Triple-Negative Breast Cancer (TNBC). Identifying biomarkers to pre-select and subclassify TNBC patients with distinct chemotherapy responses is essential. In the current study, we performed an unbiased Reverse Phase Protein Array (RPPA) on TNBC cells treated with chemotherapy compounds and found a leading significant increase of phosphor-AURKA/B/C, AURKA, AURKB, and PLK1, which fall into the mitotic kinase group. The increase of AURKA and AURKB protein was majorly due to a post-transcription level regulation, and Paclitaxel treatment induced Aurora Kinases protein phosphorylation on AURKA(T288)/AURKB(T232) sites and their protein stability. In our UAB TNBC cohort, the expression of AURKA and AURKB was significantly higher in TNBC tumors compared to normal adjacent tissues, and AURKB was found to be highly expressed in African American TNBC patients compared to European Americans. Moreover, Aurora Kinases overexpression in TNBC cells renders resistance to Paclitaxel treatment and attenuates the apoptosis effect triggered by chemotherapy treatment, suggesting Aurora Kinases could mediate the chemo-resistance in TNBC. Hence, a combination of Aurora kinase inhibitors or PROTAC degrader and taxane-type chemotherapy significantly enhanced the chemotherapy effect. In summary, we revealed that Aurora Kinases upregulation after treatment with chemotherapy could confer chemotherapy resistance to TNBC cells, and AURKB could serve as preselection markers for stratifying patients’ response to neoadjuvant chemotherapy.